1999
DOI: 10.1088/0741-3335/41/4/006
|View full text |Cite
|
Sign up to set email alerts
|

Limits of applicability of the quasilinear approximation to the lower hybrid wave-plasma interaction

Abstract: The diffusion of electrons in velocity space induced by a spectrum of electrostatic waves is numerically investigated. From the scatter of particles, the diffusion coefficient is calculated and compared with the quasilinear value. A strong disagreement is found at high electric field amplitudes, narrow spectra and short (spatial) lengths of the interaction region, which are however usual in Lower Hybrid Heating and Current Drive experiments in tokamaks. In particular, the (velocity) interaction region becomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…We note that Ref. [8] presented a relativistic extension of the exact nonlinear results of [5][6][7]. Second, we show that the standing wave interaction can be approximated by the "simplified" version of the Fermi-Ulam map [3], which we here generalize to relativistic electron velocities.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…We note that Ref. [8] presented a relativistic extension of the exact nonlinear results of [5][6][7]. Second, we show that the standing wave interaction can be approximated by the "simplified" version of the Fermi-Ulam map [3], which we here generalize to relativistic electron velocities.…”
Section: Introductionmentioning
confidence: 55%
“…To do so, we, first, extend our previous work [4][5][6][7][8] on electron phase space stochasticity caused by electrons repeatedly passing through a spatially localized travelling lower hybrid (LH) wave to the case of electrons passing through a standing wave. We note that Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the broadening of resonance observed in [1] at high electric field amplitudes is due to the overlap of neighbouring spatial modes. Further, a model of interaction of spatially localized LHW with electrons has been proposed.…”
Section: Discussionmentioning
confidence: 82%
“…In Ref. [1], we have compared this value, for a narrow spectrum of waves, with the quasilinear one [2],…”
Section: Introductionmentioning
confidence: 99%